Enamel defects and aphthous stomatitis in celiac and healthy subjects: Systematic review and meta-analysis of controlled studies - Nieri, Michele; Tofani, Elena; Defraia, Efisio; Giuntini, Veronica; Franchi, Lorenzo (Journal of dentistry, 2017)
The aim of this systematic review was to compare the presence of enamel defects and aphthous stomatitis between celiac patients and healthy controls. A systematic review of articles selected from MEDLINE, EMBASE and Google Scholar was performed by two independent operators. Additional studies hand-searched and found in the principal dental and gastroenterology journals were included. Only controlled studies on celiac patients compared to healthy subjects were included. Independent extraction of articles by 2 authors using predefined data fields, including study quality indicators. In total, the celiac patients had greater frequency of enamel defects (odds ratio=5.69, 95%CI from 3.47 to 9.33, P<0.00001, I2=90%, 30 studies). Considering only the children, the odds ratio was 5.63 (95%CI from 3.95 to 8.01, P<0.00001, I2=65%, 24 studies), while in the adults the odds ratio was not significant (odds ratio=2.16, 95%CI from 0.95 to 4.88, P=0.06, I2=40%, 3 studies). In total, the celiac patients had greater frequency of aphthous stomatitis (odds ratio=3.79, 95%CI from 2.67 to 5.39, P<0.00001, I2=49%, 21 studies). Considering only the children, the odds ratio was 4.31 (95%CI from 3.03 to 6.13, P<0.00001, I2=29%, 13 studies), while in the adults the odds ratio was 47.90 (95%CI from 6.29 to 364.57, P=0.0002, 1 study). In children, celiac disease was associated with both enamel defects and aphthous stomatitis. The odds ratio estimates, however, should be interpreted with caution due to the high risk of bias showed by all the studies. In adults, the association between celiac disease and enamel defects or aphthous stomatitis was unclear because very few studies were performed on this population. The presence of enamel defects and/or aphthous stomatitis in a child affected by other typical or atypical symptoms of celiac disease represents an indication for further diagnostic exams for celiac disease.